2022
DOI: 10.35516/hum.v49i6.3726
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Online Learning amid COVID-19 Pandemic on Student Intrinsic Motivation and English Language Improvement

Abstract: This study aims to investigate the impact of fully online learning during COVID-19 on Saudi EFL learners' intrinsic motivation and their English language improvement. It recruited 89 male and female EFL undergraduates who studied English courses at the university in the actual classroom before the pandemic and online during its outbreak. An online questionnaire was used to collect data on intrinsic motivation and English language improvement. Both the validity and reliability of the questionnaire were checked.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Furthermore, the study found that EFL students at the University of Bisha have a high level of engagement in the online classroom. This result aligns with many previous studies conducted after the onset of COVID-19 (Ali, 2022;Phuong, 2022) the shift to online learning, students have adapted to this mode of learning. Finally, the study also found a significant positive relationship between the teachers' support and the students' amount of engagement.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the study found that EFL students at the University of Bisha have a high level of engagement in the online classroom. This result aligns with many previous studies conducted after the onset of COVID-19 (Ali, 2022;Phuong, 2022) the shift to online learning, students have adapted to this mode of learning. Finally, the study also found a significant positive relationship between the teachers' support and the students' amount of engagement.…”
Section: Discussionsupporting
confidence: 92%
“…The current study used an online questionnaire to achieve the study's objectives. The researchers developed the questionnaire based on previous studies (Ali, 2022;Chiu, 2021b;Michou et al, 2023;Reeve & Shin, 2020). The questionnaire consisted of two sections.…”
Section: Instrumentmentioning
confidence: 99%
“…The instrument adopted to collect data from the participants in the study was a five-point Likert scale questionnaire. It was developed based on previous studies (e.g., Williams & Deci, 1996;Ryan & Deci, 2017;Ryan & Deci, 2019;Ali & Bin-Hady, 2019;Ali, 2022). It was divided into two sections: the first section is based on a five-point Likert scale ranging from "strongly agree" to "strongly disagree".…”
Section: Instrumentmentioning
confidence: 99%
“…It resulted from a long history of research on AI that technology-based language education drew on throughout the past decades. Early technology integration studies focused on learning strategies, motivation, attitudes, and integration into EFL and ESL programs (Ali, 2022;Al-Kadi, 2018;Ali & Bin-Hady, 2019;Zhao et al, 2002). The emergence of ChatGPT, which is "a giant autocomplete machine" (Jillian et al, 2023, p. 1), has given new areas of research on technology integration in second and foreign language education, including English (Aljanabi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The development of technology-based language teaching in recent decades has been influenced by extensive study on AI conducted over a long period of time. Prior research on technology integration mostly examined learning methodologies, motivation, attitudes, and the incorporation of technology into English as a Foreign Language (EFL) and English as a Second Language (ESL) programs (Ali, 2022; Al-Kadi, 2018; Ali & Bin-Hady, 2019; Zhao et al, 2002). The introduction of ChatGPT, referred to as a -massive autocomplete machine‖ (Jillian et al, 2023, p. 1), has opened up new avenues for studying the integration of technology in second and foreign language teaching, specifically in the context of English (Aljanabi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%